Intensive und extensive Verstädterung im Deutschen Reich zwischen 1870 und 1918 unter dem Einfluß von Bauordnungen, Bodenpreisen und Kapitalmarktverhältnissen - Böhm, Hans (ERDKUNDE, 1980)
In Germany the 1870s mark a turning point in the development of towns. After 1870 urban development was no longer regulated by a state police act, but tranferred to the communities' own responsibility. Thus different principles came to be effective where ever, as a result of the right to vote, property and land owners formed a distinct majority in the parish representations. An effective credit system for the urban sector, too, was created only after1870. The Prussian law on mortgages provided for rather low lending rates. In Prussian towns a significant share of mortgage business was therefore handled by extra-Prussian banks which were not bound by these restrictions. In the old Prussian provinces an almost 100 per cent mortgageability was facilitated by the land register classification, which had been introduced there as early as1872. In the Rhine Province and other German towns with French legal systems it was introduced only in 1900 in connection with the code of civil law. The uncertainty of proof of civil ownership and the difficulty of identifying former mortgages only permitted credits and building activities of limited extent in these areas.